Prevalence and Associated Risk Factors of Soil-Transmitted Helminth Infections among Schoolchildren around Lake Tana, Northwest Ethiopia - Melsew Getaneh; Tamirat Hailegebriel; Abaineh Munshea; Endalkachew Nibret (Journal of Parasitology Research)
Background. Soil-transmitted helminths (STHs) are among the most common neglected tropical diseases widely distributed in tropical countries with poor socioeconomic development. Ascaris lumbricoides, Trichuris trichiura, and hookworm are the three major STHs. This study aimed to determine the prevalence of STHs and associated risk factors among schoolchildren in selected primary schools around Lake Tana, Northwestern Ethiopia. Methods. A school-based cross-sectional study was conducted from February to May 2021 involving 337 study participants. A systematic random sampling method was utilized to select the study participants from the selected schools. Data related to sociodemographic characteristics of the study participants and risk factors for STH infections were collected using a pretested questionnaire. Stool samples were collected in sterile plastic containers from each participant and processed using Kato–Katz thick fecal smear and Ritchie’s concentration techniques. The data were analyzed using the Statistical Package for Social Sciences software tool version 23, and factors with a p<0.05 were considered as statistically significant. Results. The overall prevalence of STH infection was 38.3% (95% CI: 33.1–43.7). Hookworm infection was the predominant STH infection, which was detected in 26.1% schoolchildren followed by A. lumbricoides (14.8%) and T. trichiura (1.5%). Most of the study subjects (34.1%) had single infections, whereas only 4.2% study subjects had multiple helminthic infections. Among the risk factors considered in the study, lack of shoe wearing habit (adjusted odds ratio [AOR]=29.5; 95% confidence interval [CI]=6.59–132.55; p<0.001), lack of knowledge on the prevention and control methods (AOR=5.41; 95% CI = 2.44–11.98; p<0.001), engagement in irrigation activities (AOR=2.14; 95% CI = 1.02–4.57, p=0.049), lack of toilet (AOR=3.06; 95% CI = 1.31–7.16; p=0.01), children grades of 5–8 (AOR=2.62; 95% CI = 1.26–5.43; p=0.01), playing on soils (AOR=5.90; 95% CI = 2.79–12.49; p<0.001), lack of fingernail trimming habit (AOR=3.21; 95% CI = 1.57–6.55; p=0.001), and male gender (AOR=2.28; 95% CI: 1.19–4.39; p=0.013) were significant explanatory factors for STH infection among schoolchildren in the study area. Conclusions. The present study showed that STHs were common among schoolchildren around Lake Tana. Therefore, education on personal and environmental hygiene should be taken into account to reduce the prevalence of STH infection in the study area.